Socio-cultural Sustainability of Indigenous People in Kore after Two Centuries of Mount Tambora Eruption - Saddam, Saddam; Milandari, Baiq Desi; Mayasari S.W., Dian Eka; Winata, Aliahardi; Isnaini, Isnaini; Mayasari, Deviana (IJTIMAIYA: Journal of Social Science and Teaching, 2023)
The purpose of the study was to explore and analyze the socio-cultural life of the indigenous people of Korea after the two centuries of the eruption of Mount Tambora in 1815. This research uses an ethnographic approach and design in qualitative research methods. The typical phenomenon studied only exists in the Kore Tribe. The focus of this research is the socio-cultural life of the indigenous people of Kore after the 2nd century eruption of Mount Tambora. Data collection techniques use observation, interviews, and documentation. Data validity using triangulation. Data was analyzed using Miles and Huberman's interactive model. The results showed that the socio-cultural life of the indigenous people of Kore after two centuries of the eruption of Mount Tambora has changed, but there are still traditions and customs that are still maintained today. The Kore people meet Unesco standards as cultural heritage, that is, they have oral traditions, arts, social practices or traditions in our language equivalents, ceremonies or rituals, celebrations, and traditional handicrafts. However, in its development, it was influenced by many foreign cultures, especially the Mbojo (Bima) culture. Kore's oral traditions, arts, traditions, and original celebrations tend to be influenced by Mbojo culture and are even very dominant.